The effectiveness of peer assessment on students' performance in higher education. Evidence of an overview of meta-analyses - Marta Pellegrini (Firenze University Press, 2020)
The work aims to present and discuss the evidence supporting peer assessment to improve the academic performance of students in higher education by conducting an overview of meta-analyses. Meta-analyses were selected on the basis of the following selection criteria: (i) inclusion of the university context (ii) inclusion of only studies with experimental or quasi-experimental designs; (iii) description of the activities carried out in the control group during the experiment. The results show that peer evaluation has a moderate level of effectiveness on students' academic performance. Peer assessment strategies with a high level of structure that include students training on evaluation, the use of explicit and quantitative criteria and the mediation of the computer are the key elements to make peer assessment a practice of high effectiveness to enhance students' performance.   L'efficacia della valutazione fra pari sulle performance degli studenti universitari. Evidenze di una overview di meta-analisi Il contributo si propone di presentare e discutere le evidenze a supporto della valutazione fra pari per migliorare le performance accademiche degli studenti universitari attraverso la conduzione di una overview di meta-analisi. Le meta-analisi sono state selezionate sulla base dei seguenti criteri di selezione: (i) inclusione del contesto universitario (ii) inclusione di soli studi con disegni sperimentali e/o quasi-sperimentali; (iii) indicazione delle attività condotte nel gruppo di controllo durante la sperimentazione. I risultati delle due meta-analisi selezionate (Double et al., 2019, Li et al., 2020) mostrano che la valutazione fra pari ha un livello moderato di effetto sulle performance accademiche degli studenti. In particolare emerge che modalità strutturate e sistematiche che includono la formazione degli studenti alla valutazione, l'utilizzo di criteri espliciti e quantitativi, e la mediazione del computer, siano la chiave per rendere la valutazione fra pari una pratica di elevata efficacia per l'apprendimento degli studenti.